A Case Study on Gross and Net Non-performing Assets of State bank of India - Shanaliya Hetalben Jayantilal (Celebes Scholar pg, 2022)
The main objective of present study is to examine Gross non-performing assets and net non-performing assets of State Bank of India. For the present case study researcher has select five years period of study started from 2015-16 to 2019-20. Researcher has selected five NPA ratios; Gross NPA, Net NPA, Provision coverage ratio, Cash deposit ratio and Interest spread ratio. Chi- square test; time series analysis (Manually calculated) is applied on selected ratios of non-performing assets of State Bank of India. The study found out that there is no significant association in all selected ratios of state bank of India. It means in all the selected financial years ratios of non-performance assets is similar and null hypothesis is accepted. In this era banking sector has major suffer from non-performing assets. State bank of India is oldest bank with higher market capital. The paper investigates NPA of State Bank of India. This study helps to investors & managerial board for decision making.